Current and emerging strategies for the diagnosis, prevention and treatment of Lassa fever. (May 2015) - Hartnett, Jessica N; Boisen, Matthew L; Oottamasathien, Darin; Jones, Abigail B; Millett, Molly M; Nelson, Diana S; Muncy, Ivana J; Goba, Augustine; Momoh, Mambu; Fullah, Mohammed; Mire, Chad E; Geisbert, Joan B; et al.
ABSTRACT : Lassa fever (LF) is a potentially fatal disease that affects an estimated 300, 000–500, 000 people in endemic areas of west Africa each year. Though past studies have identified fatality rates of 5–20% in patients suspected to have contracted Lassa virus (LASV), new studies using more precise clinical diagnoses and modern diagnostic assays show fatalities rates above 60% in acutely ill patients from endemic regions. Currently, there are no approved vaccines or therapeutics, and only one Comformité Européenne (CE) marked rapid immunodiagnostic for acute LASV infection. Therefore, preventing LASV transmission is the primary goal in endemic regions. Development of rapid immunodiagnostics and research into the efficacy of current treatment options continues toward saving lives in west Africa as well as creating a line of defense against the nefarious use of LASV in bioterrorism settings.